Fundamentals of corporate finance - Ross, Stephen A.; Westerfield, Randolph W.; Jordan, Bradford D. (Unites States of America : Richard D. Irwin, Inc., 1995)
Fundamentals of Corporate Finance's applied perspective cements students' understanding of the modern-day core principles, giving them a problem-solving methodology and profiling real-life financial management practices-all within a clear valuation framework. A dynamic set of tools for gauging individual and class progress means educators can spend less time grading and more time teaching.
Part I. Overview of Corporate Finance -- Part II. Financial Statements and Long-Term Financial Planning -- Part III. Valuation of Future Cash Flows -- Part IV. Capital Budgeting -- Part V. Risk and Return -- Part VI. Long-term Financing -- Part VII. Cost of Capital and Long-term Financial Policy -- Part VIII. Short-term Financial Planning and Management -- Part IX. Topics in Corporate Finance .
Includes index.
Keywords: CORPORATE FINANCE